Perspectives of development healthy food institutions in the restaurant services market in Kharkiv - Danko, Natalya; Chubaka, Anastasiia (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 2020)
The article highlights the analysis of the development of a healthy nutrition system in the restaurants of the Kharkiv restaurant industry. The object is a restaurant economy, as a complex system. The subject is the organization of a healthy food restaurant. The purpose of this article is to deepen theoretical knowledge about the organization of restaurant economy in Ukraine and to identify the prospects for the development of healthy eating institutions in the market of restaurant services in the city of Kharkiv. To achieve the goal in the article, the following tasks were addressed and solved: to highlight the main theoretical concepts and normative and legal provisions of the restaurant industry; to consider overweight problems inUkraine; to analyze the European market of healthy food establishments; to study the Ukrainian market of healthy food companies; characterize the current state and prospects of the "Eathealthy" system in therestaurantindustry; to find out the format of establishments in which healthy eating can be introduced. Methods of research used during the writing of this article - analytical, comparative, research. Through the solution of the tasks, the following results were obtained: studies confirm the presence of such an incomplete segment in the restaurant market as a healthy diet. To date, there are practically no institutions in Ukraine that can offer such a menu. But the following conclusions are made that the menu "Healthy eating" can be implemented in institutions of any format. The most common is the fast food format. There-orientation of fast-food restaurants for healthy eating in Ukraine is in appropriate, since such institutions are aimed at consumers with lo win comes, and for the use of environmentally friendly raw materials and materials whose cost is high on the market, it will lose most of the customers.